Self-Healing in the Quran from a Sufi Exegetical Perspective - Lubis, Masyitoh Nur; Rambe, Irpan; Lubis, Hakimah Nur (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
This study examines the concept of self-healing in the Quran from the perspective of Sufi exegesis, focusing on three main pillars: supplication (duʿaʾ), remembrance (dhikr), and gratitude (shukr). The background of this research is rooted in the growing prevalence of mental health disorders in Indonesia, which calls for a holistic healing approach that addresses not only psychological but also spiritual dimensions. This study employs a thematic (mawduʿi) exegesis method by analyzing the interpretations of prominent Sufi scholars such as al-Qushayri, Ibn ʿArabi, and Mahmud al-Alusi on Quranic verses related to supplication, remembrance, and gratitude as forms of self-healing. The findings reveal that supplication is understood as a means of inner reconstruction and complete surrender to God that helps alleviate psychological distress; remembrance functions as a transcendental therapy that cultivates tranquility (tumaʾnnah) and prevents emotional turbulence; while gratitude serves as a mechanism for mental reinforcement by fostering positive thinking and self-acceptance. Sufi exegesis positions these three practices not merely as ritual acts, but as pathways of tazkiyat al-nafs that restore psychological balance while drawing individuals closer to God. This study concludes that self-healing from the perspective of Sufi exegesis represents an integrative healing model that combines mental, emotional, and spiritual dimensions. This model is highly relevant for addressing psychological crises in modern society, as it is grounded in enduring Quranic values.